Relaxation-Related Piezoelectric and Dielectric Behavior of Bi(Mg,Ti)O(3)–PbTiO(3) Ceramic - Park, Min Young (Sensors (Basel), 2019)
Piezoelectric and dielectric materials have attracted much attention for their functional device applications. Despite its excellent piezoelectric properties, the content of lead in piezoelectric materials should be restricted to prevent future environmental problems. Therefore, reduced lead content in piezoelectric materials with similar piezoelectric properties is favorable. In our research, piezoelectric materials with decreased lead content will be studied and discussed. Even though the lead content is decreased in Bi(Mg(0.5)Ti(0.5))O(3)–PbTiO(3) ceramics, they show piezoelectric properties similar to that of lead zirconate titanate (PZT)-based materials. We believe this high piezoelectric behavior is related to the relaxation behavior of Bi(Mg(0.5)Ti(0.5))O(3)–PbTiO(3) (BMT–PT) ceramics. In this study, 0.62Bi(Mg(0.5)Ti(0.5))O(3)–0.38PbTiO(3) ceramics were prepared by the conventional sintering process. These piezoelectric ceramics were sintered at varying temperatures of 975–1100 °C. Crystallinity and structural properties were analyzed and discussed. X-ray diffraction pattern analysis demonstrated that the optimal sintering temperature was around 1075 °C. A very high Curie temperature of 447 °C was recorded for 0.62BMT–0.38PT ceramics sintered at 1075 °C. For the first time, we found that the origin of the high Curie temperature, d(33), and the dielectric constant is the relaxation behavior of different dipoles in 0.62BMT–0.38PT ceramics.